The AskA starter kit : how to build and maintain digital reference services - Lankes, R. David (ERIC, Clearinghouse on Information & Technology, Syracuse University, 1998)
"Set of six self-instructional modules ... to create an Internet-based human-mediated information service. Real life experiences from existing digital reference services ... provide helpful hints for new services" -- back cover.